A multicentered evaluation of ablation at higher power guided by ablation index: Establishing ablation targets for pulmonary vein isolation. (6th January 2019) - Dhillon, Gurpreet; Ahsan, Syed; Honarbakhsh, Shohreh; Lim, Wei; Baca, Marco; Graham, Adam; Srinivasan, Neil; Sawhney, Vinit; Sporton, Simon; Schilling, Richard J.; Chow, Anthony; Ginks, Matthew; et al.
Abstract: Background: Pulmonary vein isolation (PVI) using high power delivered by SmartTouch Surround Flow (STSF) catheters guided by ablation index (AI) was evaluated in a multicenter registry. Methods: Patients with paroxysmal AF underwent PVI with STSF catheters using 30 W on the posterior wall and 40 W elsewhere. AI targets were 350 posterior walls and 450 elsewhere. Procedures were compared with controls using conventionally irrigated contact force‐sensing catheters using conventional powers (25 W posterior wall and 30 W elsewhere) guided by force‐time integral (no agreed targets). The waiting period of 30 minutes was observed before adenosine administration to assess acute pulmonary vein (PV) reconnection. Results: One hundred patients from four centers were included: 50 patients in the high power ablation index (HPAI) group and 50 controls. Procedure time was 22% shorter in the HPAI group (156 [133.8‐179] vs 199 [178.5‐227] minutes; P  < 0.001). Duration of the radiofrequency application was 37% shorter in the HPAI group (27.2 [21.5‐35.8] vs 43.2 [35.1‐52.1] minutes; P  < 0.001). Acute PV reconnection was reduced (28 of 200 [14%] vs 48 of 200 [24%] veins; P  = 0.015). Reconnection was predicted by a largest interlesion distance greater than 6 mm, a lesion with impedance drop less than 2.5 Ω, contact force less than 6 g, or less than 68% of the regional AI target (all P  < 0.001). Freedom from atrial arrhythmia at 1 year off antiarrhythmic drugs after a single procedure was 78% in the HPAI group vs 64% in the control group ( P  = 0.186). Conclusion: High‐powered ablation guided by AI was safe and led to shorter procedure times with reduced acute PV reconnection compared with conventional ablation.